Effects of sensory processing intervention on depression and anxiety among international students in a public university / Somayeh Khodabakhsh - Somayeh, Khodabakhsh (2016)
Depression and anxiety are among the most common psychological difficulties in adults. International students also are not immune to these problems. Studying the factors that individuals are facing in their daily life may provide information about the possible causes of these psychological difficulties. One of these factors is individuals’ sensory processing pattern, which is the way that they receive, process and respond to sensory stimuli in their daily life. Studies show, extreme patterns of sensory processing pattern affect individual’s behavior and quality of life. Considering these facts, the aim of this study was first to explore the relationship between sensory processing patterns, depression, and anxiety, and to explore which of the sensory patterns are the best predictors of depression and anxiety (First Phase of the study). The second aim was investigating the effectiveness of intervention based on sensory processing approach on depression and anxiety (Second Phase of the study). For the First Phase, 354 international postgraduate students were randomly selected and completed the study’s questionnaires including Demographic Questionnaire, Adolescent/Adult Sensory Profile®, PROMIS® Depression Item bank, and PROMIS® Anxiety Item bank. For the second phase of the study, one-group repeated-measures design was considered and the participants’ depression and anxiety were measured for four times (two pretests, a posttest, and a follow-up). Thirty-eight students who had high level of depression and anxiety in the first phase of the study participated. Four weekly intervention sessions were carried out for them based on their sensory processing patterns. As finding revealed, there is positive significant relationship between three of the sensory processing patterns and depression, including sensation avoiding (r = .31, p < .001), sensory sensitivity (r = .24, p < .001), and low registration (r = .13, p = .009). There is also positive significant relationship between sensation avoiding (r = .35, p < .001), sensory sensitivity (r = .35, p < .001) and low registration (r = .23, p = .001) and anxiety. The results showed that there is a negative significant relationship between sensation seeking and depression (r = -.12, p = .019), but the relationship between sensation seeking and anxiety is not statistically significant. Multiple regression analysis showed that sensation avoiding (β = .25, p < .05) and sensation seeking (β = .14, p < .05) are significant predictors for depression and sensory avoiding (β = .192, p < .05) and sensory sensitivity (β = .180, p < .05) are significant predictors for anxiety. The results showed that sensory processing interventions had a significant effect on reducing depression, with F(3,111) = 68.92, p < .001 and anxiety, with F(3,111) = 68.33, p < .001) between the time points. In addition, the reduction of anxiety continued even a month after the intervention sessions. The results of this study have implications for different groups of professionals in mental health and education field and for individuals themselves. In conclusion, sensory processing intervention provides sensory awareness to individuals that help them to experience lower levels of psychological difficulties.